2019
DOI: 10.1038/s41467-019-10569-3
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet-printed stretchable and low voltage synaptic transistor array

Abstract: Wearable and skin electronics benefit from mechanically soft and stretchable materials to conform to curved and dynamic surfaces, thereby enabling seamless integration with the human body. However, such materials are challenging to process using traditional microelectronics techniques. Here, stretchable transistor arrays are patterned exclusively from solution by inkjet printing of polymers and carbon nanotubes. The additive, non-contact and maskless nature of inkjet printing provides a simple, inexpensive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
222
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(224 citation statements)
references
References 44 publications
1
222
0
1
Order By: Relevance
“…The interest in OLEDs for communication is driven not only by their widespread use in display technologies but also by the very same advantages that have been driving the success of organic electronics. Above all, organic semiconductors (OSs) can be cheaply deposited over large areas, either via thermal evaporation or from solution via spin 15 , blade 16 , inkjet 17 , or spray coating 18 . Large area OS-based luminaires are already entering the market 19 and are expected to be the next mass application of OSs after active-matrix OLED (AMOLED) displays.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in OLEDs for communication is driven not only by their widespread use in display technologies but also by the very same advantages that have been driving the success of organic electronics. Above all, organic semiconductors (OSs) can be cheaply deposited over large areas, either via thermal evaporation or from solution via spin 15 , blade 16 , inkjet 17 , or spray coating 18 . Large area OS-based luminaires are already entering the market 19 and are expected to be the next mass application of OSs after active-matrix OLED (AMOLED) displays.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al demonstrated an intrinsically stretchable transistor array with a device density of 347 transistors per square centimeter . Molina‐Lopez et al used inkjet printing of polymers and carbon nanotubes to fabricate stretchable transistor arrays with mobilities of 30 cm 2 V − 1 s − 1 . The fabricated devices with and without strain are shown in Figure d,e, respectively.…”
Section: Core Components Of Fhementioning
confidence: 99%
“…Utilizing separate nozzles, different formulations of colloidal droplets can be printed side‐by‐side or stacked, forming hybrid metal‐polymer architectures. Using an entire array of semiconducting, dielectric, insulating, and conductive materials, Molina‐Lopez et al e‐jet printed arrays of stretchable field‐effect transistors (FETs) to create flexible, stretchable electronics 325. The transistors could be stretched up to 20% before diminishing in electrical performance, upon which contact separation and electrode cracking occurred.…”
Section: Electrical Patterningmentioning
confidence: 99%